The effects of temperature in the life cycle of two consecutive generations of the cuttlefish sepia officinalis (Linnaeus, 1758), cultured in the Algarve (south Portugal) - Domingues, Pedro M. (2018)
We are presently culturing the 4th generation of the cuttlefish, Sepia offıcinalis in our laboratory. A first generation (F1) was grown from eggs collected from the wild (Ria Formosa – South Portugal) during the summer, at mean temperatures of 27 °C ± 3°. In the present study, a second generation (F2), originated from eggs laid in the laboratory by females from F1 was cultured between the start of autumn and the end of spring, at mean temperatures of 15 °C ± 4 °C. The life cycle of cuttlefish from F2 was compared to F1. Populations of 30 cuttlefish were used in each experiment. Cuttlefish were grown from one day old until the cycle was completed (when the last female in each population had died). Cuttlefish from F2 cultured at much lower temperatures had a longer life cycle, of almost 9 months (260 days) compared to cuttlefish from F1, which completed their cycle in less than 6 months (165 days). Cuttlefish from F2 grew significantly larger (U = 0.00; p < 0.01) with mean weights of 343.3 ± 80.5 g and 248 ± 33.1 g for males and females, respectively, compared to F1 (199.6 ± 40 g and 143.3 ± 30.9 g for males and females, respectively). Females from F2 had higher fecundity (225 eggs female− 1) compared to females from F1 (144 eggs per female−1), produced bigger eggs (t = 45.60752; p < 0.0001), weighing 0.74 ± 0.18 g, compared to 0.46 ± 0.11 from F1, and bigger hatchlings (t = 7,144783; p < 0.0001), weighing 0.10 ± 0.02 g, compared to 0.09 ± 0.02 g for the summer population.